Effect of Ozone on Antagonistic Activity of Lactobacilli - Anzor A. Ismailov (Journal of Global Pharma Technology, 2020)
This article describes study results that confirm the effect of ozone on the antagonistic effect of Lactobacillus plantarum 8P-A3 against Bacillus subtilis, Escherichia coli and Candida albicans test cultures. A stable (within 48 hours) dose-dependent effect on lactobacilli antagonistic activity was proven; it was maintained in all used ozone concentrations (from ˂0.29 mg/L, 0.29 mg/L, 0.38 mg/L). It was found that the intensity of lactic acid formation which is the most important criterion for lactobacilli antagonistic activity is significantly higher at the ozone concentration of ˂0.29 mg/L than in control samples; herewith the bacterium retains the properties of a strong antagonist. Level of lactic acid at the doses of 0.29 mg/L and 0.38 mg/L is reduced in comparison to control samples, and lactobacilli can be characterized as weak antagonists.Keywords: Antagonistic activity of lactobacilli, Antagonistic factors, Ozone, Effect of ozone on microorganisms, Lactic acid.